High-resolution profiling of the gut microbiome reveals the extent of Clostridium difficile burden. (December 2017) - Daquigan, Ninalynn; Seekatz, Anna; Greathouse, K.; Young, Vincent; White, James
Abstract Microbiome profiling through 16S rRNA gene sequence analysis has proven to be a useful research tool in the study ofC. difficile infection (CDI); however, CDI microbiome studies typically report results at the genus level or higher, thus precluding identification of this pathogen relative to other members of the gut microbiota. Accurate identification ofC. difficile relative to the overall gut microbiome may be useful in assessments of colonization in research studies or as a prognostic indicator for patients with CDI. To investigate the burden ofC. difficile at the species level relative to the overall gut microbiome, we applied a high-resolution method for 16S rRNA sequence assignment to previously published gut microbiome studies of CDI and other patient populations. We identifiedC. difficile in 131 of 156 index cases of CDI (average abundance 1.78%), and 18 of 211 healthy controls (average abundance 0.008%). We further detected substantial levels ofC. difficile in a subset of infants that persisted over the first two to 12 months of life. Correlation analysis ofC. difficile burden compared to other detected species demonstrated consistent negative associations withC. scindens and multipleBlautia species. These analyses contribute insight into the relative burden ofC. difficile in the gut microbiome for multiple patient populations, and indicate that high-resolution 16S rRNA gene sequence analysis may prove useful in the development and evaluation of new therapies for CDI. C. difficile : Investigating infection in the gut A detailed analysis of the prevalence of the bacteriumClostridium difficile in the gut will aid research and could improve clinical care.C. difficile infection is a major global healthcare problem, causing 29, 000 deaths each year in the USA alone. It is frequently acquired by hospitalized patients, especially after antibiotic treatment. Researchers in the USA, led by James White at Resphera Biosciences in Baltimore, Maryland, used high-resolution 16S rRNA sequence analysis of gut microbial communities to characterizeC. difficile levels in several patient populations. The results gave insights into the burden ofC. difficile during infection relative to healthy control populations. They also revealed substantial levels ofC. difficile in some infants through the first year of life. The authors suggest the analysis technique they used may help guide the development of new treatments for these difficult infections.